1996
DOI: 10.1212/wnl.47.3.788
|View full text |Cite
|
Sign up to set email alerts
|

Late motor deficits of Chilean manganese miners

Abstract: High-level chronic manganese (Mn) exposure produces dystonic rigidity and proximal tremor. The late effects of asymptomatic exposure are uncertain. To evaluate hand movements of asymptomatic Chilean miners, we utilized a manual tremormeter (EAP) and a digitizing tablet (MOVEMAP). In Andacollo, Chile, we examined 59 individuals aged > 50 years (mean age, 64.4 years). Twenty-seven exposed miners had heavy Mn dust exposure in Mn mines for more than 5 years (mean duration, 20.25 years), ending at least 5 years pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 6 publications
1
23
0
1
Order By: Relevance
“…The MOVEMAP system [Hochberg et al, 1996], consists of a digitizing tablet connected to a computer, and was used by Gibbs et al [1999] who administered the Steady Movemap Test, designed to quantify resting tremor of the wrist and hand, and the Square Movemap Test, designed to quantify action tremor of the wrist and hand. These [Matthews et al, 1994]: results indicated impaired tremor parameters (number and duration of contacts) among Mn workers.…”
Section: Occupational Studies: Motor Functionsmentioning
confidence: 99%
“…The MOVEMAP system [Hochberg et al, 1996], consists of a digitizing tablet connected to a computer, and was used by Gibbs et al [1999] who administered the Steady Movemap Test, designed to quantify resting tremor of the wrist and hand, and the Square Movemap Test, designed to quantify action tremor of the wrist and hand. These [Matthews et al, 1994]: results indicated impaired tremor parameters (number and duration of contacts) among Mn workers.…”
Section: Occupational Studies: Motor Functionsmentioning
confidence: 99%
“…In an early study carried out by Jonderko et al (1971) on a group of active workers from a ferromanganese foundry with high serum Mn levels, who were removed from exposure, most showed no change over a 2-year period, 13.5% showed improvement, and 24.3% presented some form of health deterioration as measured by subjective symptom reporting and neurological examination. More recently, long-term effects of manganese following cessation of exposure have been examined among Chilean miners, who had not been exposed over the past 5 years (Hochberg et al, 1996). A higher prevalence of resting and action tremor and poorer repetitive hand movements was observed among the miners formerly exposed to manganese than among miners who had not been exposed to this metal.…”
Section: Workplace Studiesmentioning
confidence: 99%
“…It should be noted however, that multiple other PD cases have been screened and they did not harbor mutations (Giasson et al, 2000), but gene mutations may serve as vulnerable markers, superimposed by environmental factors and age-related wear-and-tear. The root-cause of idiopathic PD is unknown, but various factors are implicated, including the oxidation of dopamine, free radical-mediated oxidative injury, mitochondrial abnormalities, excitotoxins, over exposure to manganese (Chu et al, 1995;Hochberg et al, 1996) and carbon monoxide, the intake of beta-methylaminoalanine (Spencer, 1987), benzyl-tetra-hydroisoquinolines and tetra-hydroprotoberines (CaparrosLefebvre and Steele, 2005), 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (Davis et al, 1979), methanol (Guggenheim et al, 1971). As well as the potent methylating agent, methylazoxymethanol (Ince and Codd, 2005) and excess methylation via high utilization of the endogenous S-adenosyl-L-methionine in the brain (Charlton and Way, 1978;Charlton et al, 1992;Charlton and Mack, 1994).…”
Section: Major Symptoms and The Proposed Causes For Parkinson's Diseasementioning
confidence: 99%